The reluctant psychic : a memoir - Saxman, Suzan (St. Martin's Press, 2015)
We all, as children, saw imaginary friends and heard monsters in the closet. But for Suzan Saxman, those friends and monsters didn't go away--and they weren't imaginary. They were the dead who came to her from the time she was a little girl with urgent messages for the living. Raised in a house filled with secrets, she saw and spoke the truth as soon as she could talk, alarming the nuns in her convent school with her revelations and terrifying her own mother with her strange visions. Each night she woke to see a man with no eyes watching her, and each day she kept watch by the window while her father was at work and Steve, her real father, a swarthy drifter, rendezvoused with her mother. It was the 1960s in suburban Staten Island and she tried to hide it all, and be a daughter her mother could love.